EVALUATING THE CONTRIBUTION OF ORGANIC FARMING TO CLIMATE RESILIENCE IN NAGAPATTINAM DISTRICT, TAMIL NADU - M. SANTHIYA; D. MURUGAN (The Bioscan, 2025)
This study titled “Evaluating the Contribution of Organic Farming to Climate Resilience in Nagapattinam District, Tamil Nadu” investigates how organic farming practices strengthen agricultural resilience against climate-related stresses. The objective was to examine the role of organic methods in improving soil health, enhancing water management, and increasing farmers’ adaptive capacity. Guided by the research question, “How do organic farming practices contribute to climate resilience among farmers in Nagapattinam district?” the study employed a mixed-method approach combining quantitative surveys, laboratory soil and water analysis, and qualitative interviews with 200 farmers selected through stratified random sampling. Descriptive and inferential statistics, including correlation and regression analyses, were applied to evaluate relationships between organic practices and resilience indicators. The results revealed that organic farming significantly improved soil fertility (r = 0.62), water-use efficiency (r = 0.68), and adaptive capacity (R² = 0.61). The findings validated all four hypotheses, confirming that higher levels of organic adoption lead to enhanced climate resilience. Policy suggestions emphasize institutional support, financial incentives, and stronger market linkages for promoting organic agriculture. The study concludes that organic farming offers an effective, sustainable, and locally adaptable solution to mitigate the adverse impacts of climate change while ensuring long-term livelihood security for coastal farmers in Tamil Nadu.